2019
DOI: 10.1111/2041-210x.13141
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Mantel statistic with a spatially‐constrained permutation procedure

Abstract: Mantel tests are widely used in ecology to assess the significance of the relationship between two distance matrices computed between pairs of samples. However, recent studies demonstrated that the presence of spatial autocorrelation in both distance matrices induced inflations of parameter estimates and type I error rates. These results also hold for partial Mantel test which is supposed to control for the spatial structures. To address the issue of spatial autocorrelation in testing the Mantel statistic, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 39 publications
(54 reference statements)
2
45
0
1
Order By: Relevance
“…resistant species), notably for stream invertebrates (e.g. Aspin et al, 2018;Crabot, Clappe, et al, 2019;Datry et al, 2014;Leigh & Datry, 2017) but also for algae (Robson & Matthews, 2004;Robson, Matthews, Lind, & Thomas, 2008), our result confirms that drying can have, in some cases, a legacy effect long after rewetting. Here, drying reaches were still exhibiting a lower taxonomic richness than perennial reaches even after up to 6-9 months of flowing conditions.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…resistant species), notably for stream invertebrates (e.g. Aspin et al, 2018;Crabot, Clappe, et al, 2019;Datry et al, 2014;Leigh & Datry, 2017) but also for algae (Robson & Matthews, 2004;Robson, Matthews, Lind, & Thomas, 2008), our result confirms that drying can have, in some cases, a legacy effect long after rewetting. Here, drying reaches were still exhibiting a lower taxonomic richness than perennial reaches even after up to 6-9 months of flowing conditions.…”
Section: Discussionsupporting
confidence: 81%
“…In general, ecologists are using either proxies for dispersal (e.g. using biological traits, Aspin et al, 2018;Crabot, Clappe, et al, 2019) or statistical tools (e.g. distance-decay relationships, variance partitioning) to unravel its roles F I G U R E 3 Alpha-diversity distribution (mean ± standard deviation) for perennial (black circle) and intermittent (grey triangle) reaches for each fragmented headwater and for both sampling period (before and after the drying season) Table 2 for exact values of r) for each combination of community type (Chao dissimilarity index) and distance matrices for each fragmented headwater (FHW) before and after the drying season, for the whole community (a), the community of taxa with aerial stages (b), and strictly aquatic taxa (c).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the presence of spatial autocorrelation between distance matrices may cause Mantel test results to have an inflated Type I error, that is, rejecting the null hypothesis even though it is true (Guillot and Rousset, 2013). Partial Mantel tests are often used to control for an underlying spatial matrix, but research has suggested that partial Mantel tests may not be adequate for controlling for spatial autocorrelation (Guillot and Rousset, 2013;Crabot et al, 2019). Future research focused on how abiotic (physical distance, local environment) and biotic (competition, predation, symbiosis) factors interact will provide more insight to the different roles that each factor plays in shaping metacommunities (Chiu et al, 2020).…”
Section: Influence Of Connectivity On Dispersal and Metacommunitiesmentioning
confidence: 99%
“…Separate models were created for each of the four dragonfly responses (abundance, biomass, diversity and assemblage). Because increasing the number of variables in partial Mantel models is known to inflate type I error rates 46 , we chose to only assess high-level models using this approach and applied false discovery rate corrections to path p -values within each model to account for multiple comparisons 47 . In order to assess the associations between specific environmental variables and dragonfly responses, we developed distance-based linear models (DistLM) in PRIMER 7 48 using a step-wise procedure and Akaike Information Criterion with corrections (AICc) to find the best fitted model even with a large number of predictor variables.…”
Section: Methodsmentioning
confidence: 99%